2013
DOI: 10.4314/star.v1i4.98818
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Drinking Water Sources in Rural Communities of Dire Dawa Administrative Council

Abstract: Article InformationIn Ethiopia, access to improved water supply and sanitation was estimated at 38% and 12% respectively. Three-forth of the health problems of children in Ethiopia are communicable diseases due to polluted water and improper water handling practices. Thus, this study was conducted to assess the microbiological quality of drinking water sources in rural communities of Dire Dawa Administrative Council (Adada Peasant Association). A cross-sectional study was conducted from February 2011 to May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
2
14
2
Order By: Relevance
“…In this study, we found that about 10% of all bacteriological samples were positive for total coliforms and fecal coliforms. This finding was lower than the studies finding in Jimma and Dire Dawa Ethiopia [8,9]. This difference may be AAWSA controls the safety and quality of water through evaluation of water sources and manage contamination of water supply.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In this study, we found that about 10% of all bacteriological samples were positive for total coliforms and fecal coliforms. This finding was lower than the studies finding in Jimma and Dire Dawa Ethiopia [8,9]. This difference may be AAWSA controls the safety and quality of water through evaluation of water sources and manage contamination of water supply.…”
Section: Discussioncontrasting
confidence: 58%
“…In Ethiopia studies conducted in Dire Dawa and Jimma revealed 83.34% and 87.5% of water sample were positive for bacterial indicators respectively [8,9]. Additionally, a study done in North Gondar showed that springs (35.7%), protected wells (28.6%), and water lines (50%) had Escherichia coli [10].…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with Tadesse et al (2010) who performed a rapid water quality assessment in Ethiopia from 2004 to 2005 and indicated that only 58.6% improved water sources respect the WHO guideline value for total coliform bacteria. In Dire Dawa City Administrative Council, Ethiopia, a bacteriological water quality analysis was conducted by Amenu et al (2012) from protected springs and wells, and the result demonstrates that 85% of water samples taken were positive for indicator bacteria. In the Dominican Republic, the assessment of microbial quality of improved drinking water showed that the quality of water was poor with more than 90% of the water samples contaminated with E. coli bacteria and 47% of samples were having high and very high sanitary risk to human health (Baum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This community-based cross-sectional survey depicted that childhood parasitic infection was statistically associated with unprotected drinking water sources which is congruent with the findings of other studies [ 36 41 ]. This can be justified that unprotected sources are prone to contamination with different wastes and pathogenic organisms like cysts of protozoon species and eggs of worms which commonly transmitted to human by ingesting of contaminated water [ 42 45 ].…”
Section: Discussionmentioning
confidence: 99%